Okostje brazdastega kita v Prirodoslovnem muzeju Slovenije - Jernejc Kodrič, Mojca (Scopolia, 2012)
In March 2003, the Slovenian Museum of Natural History acquired a 13.2 m long female Fin Whale (Balaenoptera physalus), which had been found as a floating carcass in Piran Bay, Slovenia. The procedures associated with the acquisitionof formal permits for the adoption of the carcass are described, as well as for its immersion to a depth of about 20 metres, where left to its natural decomposition. Thereupon, its bones were lifted to the surface, desalinated, fat removed from them through chemical extraction with organic dichloromethane solvent, and consolidated. In 2011, the whale's skeleton was assembled from individual bones. On September 15th of the same year, it was finally exhibited within the framework of the 190th anniversary of the Provincial Museum of Carniola, direct predecessor of the Slovenian Museum of Natural History. The article describes and photographically presents the Fin Whale's individual bones. The last chapter is dedicated to the planning and implementation of the exhibition in the context of natural heritage interpretation, the accompanying programmes, promotion and evaluation of the exhibition.
Keywords: zoologija; zoology; kiti; whales; Balaenoptera physalus; osteology; Jadransko morje; museology; museum exhibition; skeletiranje; Slovenia; osteologija; muzeologija; muzejska razstava; interpretacija; Slovenija; Adriatic Sea; maceration; interpretation